THE USE OF TONGUE TWISTER TECHNIQUE TO IMPROVE STUDENTS’ PRONUNCIATION - Awalia Azis; Abd Rajab; Dzur Rif’ah; Hilda Hafid (Universitas Muhammadiyah Makassar, 2021)
The objective of this research was to find out whether the use of tongue twister technique can improve students’ pronunciation especially in pronouncing sound /ð/, /d/, /θ/, /t/, /ᶴ/, and /s/ or not.The method of this research was pre-experimental with pre-test and post-test as an instrument of the research. The population of the research was the eleventh grade of SMP 2 Sungguminasa that consisted of 63 students. The number of samples was 33 students. The data collection consisted of pre-test, treatment and post-test. Forms of pre-test and post-test were oral test that contained 18 words that related with the focus sounds.The findings of the research showed that the students’ mean score of pre-test before treatment was 63.09%. While after treatment, the mean score of post-test was 86.81%. Therefore, the significant between pre-test and post-test was 37.59%. In order that, the researcher assumed that using tongue twister technique could improve students’ pronunciation correctly especially in pronouncing sound /ð/, /d/, /θ/, /t/, /ᶴ/, and /s/.